A Quantitative Perspective of Alpha-Synuclein Dynamics – Why Numbers Matter - Specht, Christian G. (Frontiers in Synaptic Neuroscience, 2021)
The function of synapses depends on spatially and temporally controlled molecular interactions between synaptic components that can be described in terms of copy numbers, binding affinities, and diffusion properties. To understand the functional role of a given synaptic protein, it is therefore crucial to quantitatively characterise its biophysical behaviour in its native cellular environment. Single molecule localisation microscopy (SMLM) is ideally suited to obtain quantitative information about synaptic proteins on the nanometre scale. Molecule counting of recombinant proteins tagged with genetically encoded fluorophores offers a means to determine their absolute copy numbers at synapses due to the known stoichiometry of the labelling. As a consequence of its high spatial precision, SMLM also yields accurate quantitative measurements of molecule concentrations. In addition, live imaging of fluorescently tagged proteins at synapses can reveal diffusion dynamics and local binding properties of behaving proteins under normal conditions or during pathological processes. In this perspective, it is argued that the detailed structural information provided by super-resolution imaging can be harnessed to gain new quantitative information about the organisation and dynamics of synaptic components in cellula. To illustrate this point, I discuss the concentration-dependent aggregation of α-synuclein in the axon and the concomitant changes in the dynamic equilibrium of α-synuclein at synapses in quantitative terms.